Cerebral Perfusion Long Term after Therapeutic Occlusion of the Internal Carotid Artery in Patients Who Tolerated Angiographic Balloon Test Occlusion - Gevers, S. (AJNR Am J Neuroradiol, 2012)
BACKGROUND AND PURPOSE: Therapeutic carotid occlusion is an established technique for treatment of large and giant aneurysms of the ICA, in patients with synchronous venous filling on angiography during BTO. Concern remains that hemodynamic alterations after permanent occlusion will predispose the patient to new ischemic injury in the ipsilateral hemisphere. The purpose of this study was to assess whether BTO with synchronous venous filling is associated with normal CBF long term after carotid sacrifice. MATERIALS AND METHODS: Eleven patients were included (all women; mean age, 50.5 years; mean follow-up, 38.5 months). ASL with single and multiple TIs was used to assess CBF and its temporal characteristics. Selective ASL was used to assess actual territorial contribution of the ICA and BA. Collateral flow via the AcomA or PcomA or both was determined by time-resolved 3D PCMR. Paired t tests were used to compare CBF and timing parameters between hemispheres. RESULTS: Absolute CBF values were within the normal range. There was no significant CBF difference between hemispheres ipsilateral and contralateral to carotid sacrifice (49.4 ± 11.2 versus 50.1 ± 10.1 mL/100 g/min). Arterial arrival time and trailing edge time were significantly prolonged on the occlusion side (816 ± 119 ms versus 741 ± 103 ms, P = .001; and 1765 ± 179 ms versus 1646 ± 190 ms, P < .001). Two patients had collateral flow through the AcomA only and were found to have increased timing parameters compared with 9 patients with mixed collateral flow through both the AcomA and PcomA. CONCLUSIONS: In this small study, patients with synchronous venous filling during BTO had normal CBF long term after therapeutic ICA occlusion.